Cholesterol Sulfate Exerts Protective Effect on Pancreatic β-Cells by Regulating β-Cell Mass and Insulin Secretion - Zhang, Xueping; Deng, Dan; Cui, Daxin; Liu, Yin; He, Siyuan; Zhang, Hongmei; Xie, Yaorui; Yu, Xiaoqian; Yang, Shanshan; Chen, Yulong; Su, Zhiguang (Frontiers in Pharmacology, 2022)
Rational: Cholesterol sulfate (CS) is the most abundant known sterol sulfate in human plasma, and it plays a significant role in the control of metabolism and inflammatory response, which contribute to the pathogenesis of insulin resistance, β-cell dysfunction and the resultant development of diabetes. However, the role of CS in β-cells and its effect on the development of diabetes remain unknown. Here, we determined the physiological function of CS in pancreatic β-cell homeostasis. Materials and Methods: Blood CS levels in streptozotocin (STZ)- or high-fat diet-induced diabetic mice and patients with type 1 or 2 diabetes were determined by LC-MS/MS. The impact of CS on β-cell mass and insulin secretion was investigated in vitro in isolated mouse islets and the β-cell line INS-1 and in vivo in STZ-induced diabetic mice. The molecular mechanism of CS was explored by viability assay, EdU incorporation analysis, flow cytometry, intracellular Ca2+ influx analysis, mitochondrial membrane potential and cellular ROS assays, and metabolism assay kits. Results: Plasma CS levels in mice and humans were significantly elevated under diabetic conditions. CS prevented diabetes in a low-dose STZ-induced mouse model. Mechanistically, CS promoted β-cell proliferation and protected β-cells against apoptosis under stressful conditions, which in turn preserved β-cell mass. In addition, CS supported glucose transporter-2 (GLUT2) expression and mitochondrial integrity, which then resulted in a less reactive oxygen species (ROS) generation and an increase in ATP production, thereby enabling insulin secretion machinery in the islets to function adequately. Conclusions: This study revealed a novel dual role of CS in integrating β-cell survival and cell function, suggesting that CS might offer a physiologic approach to preserve β-cells and protect against the development of diabetes mellitus.